Study on the Power Performance of Hybrid Electric Vehicle with Rear twin-shaft Type AMT - Song Jun; Chu Chaomei; Tang Haichuan; Chen Jiejing (Jixie chuandong)
AMT is used in hybrid electric vehicle,and the motor and gearbox output shaft coupling rear twin-shaft type structure is adopted,so during the shifting time,the motor will provide power to drive the car,which play the advantages of high transmission efficiency,great capacity of torque and continuous output can play as stepless transmission power strength,and the power performance is improved.By solving the motor power torque during the process of shift,the vehicle simulation model is established in the Avl- Cruise and electric auxiliary strategy of vehicle is built in the MATLAB / Simulink for united simulation studying.The simulation results show that,in the process of shifting,the vehicle acceleration is not obvious drop,at the same time,the speed maintain upward trend,the power performance of vehicle can be improved.